Corporations, human rights and the environmental degradation–corruption nexus. Issue 1 (May 2019) - Huisman, Wim; Sidoli, Daniel
Abstract : It is often the case that harms to societies go hand in hand. This seems to be true when looking at cases in which corporations are accused of contributing to human rights abuses, environmental degradation and corruption in developing nations. This article considers the relationships between these three harms from the perspective of corporations as actors involved in producing those harms. Based on a cross-case analysis of 45 cases in which this nexus of harms is found, this article assesses the atrocity crimes/environmental degradation/corruption-nexus, by studying agency (crime scripts), actors (industries and corporations) and connections (how are the three harms related?) in these cases. The analysis shows that corporations are mostly indirectly involved in atrocity crimes, but directly involved in environmental harm and corruption. Extractive industries are overrepresented and the many entanglements with state agents qualify as state-corporate crime. The relations between the harms are multifaceted and can be causal, spurious and synonymous by nature.